1995
DOI: 10.2307/4003057
|View full text |Cite
|
Sign up to set email alerts
|

Mountain Big Sagebrush Browse Decreases Dry Matter Intake, Digestibility, and Nutritive Quality of Sheep Diets

Abstract: A metabolism study evaluated the influence of increasing quantities (O-30% dry matter basis) of mountain big sagebrush (Artemisia trident&a ssp. vaseyana Rydb. Beetle) on dry matter intake and in vivo digestibility of wether diets. Diets consisted of band-harvested, coarse-ground and frozen current year's growth of mountain big sagebrush leaves and twig tips mixed with chopped native grass hay. Dry matter intake decreased from 93 to 23 g dry matter day" kg metabolic weight' and in vivo dry matter digestibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…Thus, we hypothesize terpenes set a limit on the amount of food lambs consumed (i.e., toxin satiation). This hypothesis is consistent with the observation that lambs eating sagebrush/grass diets limited terpenoid ingestion to 170 mg/kg metabolic weight/day (Ngugi et al 1995) and that toxins can limit the amount of foods lambs can ingest (Launchbaugh et al 1993, Wang andProvenza 1997).…”
Section: Exposure Early In Lifesupporting
confidence: 83%
See 2 more Smart Citations
“…Thus, we hypothesize terpenes set a limit on the amount of food lambs consumed (i.e., toxin satiation). This hypothesis is consistent with the observation that lambs eating sagebrush/grass diets limited terpenoid ingestion to 170 mg/kg metabolic weight/day (Ngugi et al 1995) and that toxins can limit the amount of foods lambs can ingest (Launchbaugh et al 1993, Wang andProvenza 1997).…”
Section: Exposure Early In Lifesupporting
confidence: 83%
“…Animals forced to eat a ration of 30% sagebrush show marked depression in in vivo dry matter digestibility (Ngugi et al 1995). Reduced microbial activity decreases digestibility of macronutrients and byproducts of fermentation (i.e., volatile fatty acids), all of which affect food preferences of sheep (Villalba and Provenza 1996, 1997a, 1997b, 1997c.…”
Section: Nutritional Statementioning
confidence: 99%
See 1 more Smart Citation
“…In the 1998 trial, frozen diets caused a small decrease of forage intake (Fraker 1999), which was associated with an increase in average H and greater deviation from unity of the slope (i.e,1.27 and 1.43 for the dry and frozen diets, respectively). Ngugi et al (1995) reported a much BW on the 0% sagebrush diet to 9 g/kg greater effect of percent sagebrush in the BW on the 30% sagebrush diet with a condiet on intake and digestibility for the comitant decline in apparent dry matter Wyoming trial than was reported for the digestibility of from 59 to -3% in this 1998 trial. Intake declined from 38 g/kg study.…”
Section: Resultsmentioning
confidence: 53%
“…Age, sex, or physiological status of the animal could affect fecal composition via the effect these factors have on intake and digestibility. Furthermore, the amount of sagebrush in the diet affects both intake and digestibility (Ngugi et al 1995), and these effects are greater for fresh compared to dried sagebrush (Fraker 1999). Typically 60% or more of ruminant feces is composed of metabolic products including bacteria and endogenous waste (Van Soest 1982).…”
Section: Resultsmentioning
confidence: 99%